Pluralism from the phenomenological "reason" - San Martín, Javier (Estudios de Filosofía, 2008)
In a recent and extremely interesting Congress organized by the Nordic Society of Phenomenology and the Lithuanian Society of Phenomenology, I exposed, in one of the six plenary sessions, the fundamentals and basics of the Husserlian phenomenology of reason when founding the human sciences. The two fundamental elements of this phenomenology of reason are, on the one hand, the Husserlian description that comes from the Ideas of 1913, that in the gift that occurs in perception there is a foundation of reason, because perception gives us He gives things in person, therefore, in what we could rightly call, in themselves, in what Ortega will interpret correctly, as in his enforceability, which does not prevent Husserl from being a deep reader of William James In that perception of the Urdoxa, the original belief, because every perception and every judgment of reality that is based on a perception implies a belief that we are right, that what is perceived and affirmed will continue to behave in that way. [Fragment]